Experiential learning and outdoor education traditions of practice and philosophical perspectives - Allison, Pete; Parry, S. J. (S. Jim) (Routledge, 2020)
This book adds to the theoretical development of the emerging fields of experiential learning and outdoor education by examining the central concept, 'experience', and interrogating a central claim of experiential learning: whether, and if so how, a short-term singular experience can transform a participant's life as a whole and in a permanent way. While such a possibility has been corroborated by the personal testimonies of participants, and the activities of instructors over many years, the book argues that we must go beyond this kind of evidence'. In comparing Anglophone and continental approaches and drawing on the work of Dewey, Dilthey and Merleau-Ponty in the philosophy of experience, Experiential Learning and Outdoor Education presents the first detailed review of the concept of experience' in European philosophy, as applied to outdoor experiential learning. A vital insight into the field, this is important reading for students and researchers working in the philosophy of sport, and pedagogical theory, especially in areas relating to the outdoors, but also to experiential education more generally